PRImary care Streptococcal Management (PRISM) study : in vitro study, diagnostic cohorts and a pragmatic adaptive randomised controlled trial with nested qualitative study and cost-effectiveness study /: in vitro study, diagnostic cohorts and a pragmatic adaptive randomised controlled trial with nested qualitative study and cost-effectiveness study. (January 2014) - Prof, Little, P (Paul)
No abstract available